Supervisi Kepala Sekolah Berbasis Kepemimpinan Transformasional Meneladani Umar bin Khattab dalam Meningkatkan Kinerja Guru di Sekolah Dasar - Ahmad Faoji; Pepen Suhendra (Tashfiyatuna: Jurnal Pendidikan Keislaman, 2025)
This study examines a Transformational Leadership-Based Principal Supervision Model inspired by the values of Umar bin Khattab at an Islamic elementary school in Bekasi. Using a descriptive qualitative approach, it analyzes how principals integrate justice (‘adl), trust, and deliberation into supervision, and how transformational leadership dimensions—idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration—shape teacher performance. Findings show that supervision grounded in exemplary leadership enhances motivation, professionalism, and a climate supportive of innovation. Umar’s values provide ethical and operational foundations that strengthen fairness, accountability, and teacher participation. However, successful implementation requires balance between evaluation and coaching, adequate resources, and alignment with school culture. Overall, the model demonstrates potential for replication in other elementary schools aiming to improve learning quality.